Digital Notice Board using Bluetooth and Arduino - Rajeshwari, S.; Ushasree, R; C., Fong Kim (INTI International University, 2024)
In this project, Bluetooth and Arduino microcontrollers are used to build and operate a wireless noticeboard system. To disseminate real-time information across many contexts, a cutting-edge, interactive platform is now being developed. On conventional noticeboards, there are just physical notes and human modifications, both of which can be tedious and time-consuming. This solution makes use of Bluetooth connectivity and the adaptability of Arduino to let users send messages wirelessly from their cell phones or laptops. The Bluetooth-enabled devices used in the wireless noticeboard system allow users to enter messages. An Arduino microcontroller with a Bluetooth module collects the messages, processes them, and displays the results on a display device. Users can rapidly post messages to the noticeboard from their mobile devices using Bluetooth technology without having to engage with it physically. The system's core processing unit, the Arduino microcontroller, which also activates the display unit, receives and processes incoming messages before displaying them.